2002
DOI: 10.1289/ehp.021101233
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of techniques to reduce residential lead dust on carpet and upholstery: the new jersey assessment of cleaning techniques trial.

Abstract: High-efficiency particulate air (HEPA) filtered vacuum cleaners are recommended by the U.S. Department of Housing and Urban Development for cleaning lead-contaminated house dust. We performed a randomized field study to determine whether a conventional (non-HEPA) vacuum cleaner could achieve cleaning results comparable with those of a HEPA vacuum cleaner. We compared the lead loading reductions of these two vacuum cleaners in a total of 127 New Jersey homes of lead-exposed children. We used wet towelettes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 18 publications
0
9
1
Order By: Relevance
“…The most reasonable explanation, then, is that the accumulated dust commonly seen on relatively inaccessible surfaces in the house remains relatively undisturbed by air currents, ventilation or household activities. Carpets have been reported to be an important potential secondary source of lead-laden dust in other settings 25,33,34) but were not found in the households in this study.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…The most reasonable explanation, then, is that the accumulated dust commonly seen on relatively inaccessible surfaces in the house remains relatively undisturbed by air currents, ventilation or household activities. Carpets have been reported to be an important potential secondary source of lead-laden dust in other settings 25,33,34) but were not found in the households in this study.…”
Section: Discussioncontrasting
confidence: 63%
“…However, the levels of lead in soil might be expected to be influenced by natural dispersal effects similar to those contributing to household surface lead contamination. Previous studies have shown that soil lead content peaked at the locations of a boat repair yard 7) , a former lead smelter 19,37,38) and a lead battery manufacturing plant 34) , with soil lead content decreasing with increasing distance from the point source. Lead-contaminated exterior soil has been reported to be a contributing source of interior lead dust [39][40][41] .…”
Section: Discussionmentioning
confidence: 92%
“…The study found that approximately 20% of the linoleum surface dust was recoverable with a final wet washing using tap water and a sponge. Despite differing levels of performance by vacuum cleaners, vacuum cleaner removal of dirt from flooring (notably from carpeted floors) has frequently been advocated (see, e.g., Roberts et al 1999;Yiin et al 2002). The type of incomplete surface removal of surface material identified here has been seen elsewhere.…”
Section: Discussionmentioning
confidence: 88%
“…One may use a vacuum cleaner with a HEPAfilter combined with cyclone technology to remove particles as small as 0.3 lm to prevent small Cd-loaded particles from being remitted into the air (Yiin et al 2002). For most of these preventive measures no hard scientific evidence based on intervention studies exists.…”
Section: Preventionmentioning
confidence: 99%